Mechanisms for enhanced plasticity in magnesium alloys. (1st January 2015) - Zhu, S.Q.; Yan, H.G.; Liao, X.Z.; Moody, S.J.; Sha, G.; Wu, Y.Z.; Ringer, S.P.
Abstract: We have recently reported that a high strain-rate rolling process is effective for producing strong and ductile Mg alloy sheets. Here we elucidate the fundamental mechanisms that are responsible for plastic deformation in this process via systematic physical thermomechanical plane-strain rolling simulations on a Mg–Zn–Zr alloy. The strain-rate sensitivities of the alloy's microstructure and flow curves were closely correlated to the onset of deformation twinning and dynamic recrystallization (DRX). Unlike deformation at low strain rates, deformation at the high strain rates applied here induced a high number density of twins, including a predominance of 1 0 1 ¯ 1 – 1 0 1 ¯ 2 double twins in coarse grains, and a predominance of 1 0 1 ¯ 2 twins in fine DRX grains. We also report a new observation of 1 0 1 ¯ 2 nanotwins in ultrafine grains with high density in bulk Mg alloy when processed at high strain rates. We propose that the high propensity for twinning at high strain rates provides nucleation sites for DRX, resulting in a uniform, ultrafine-grained microstructure that exhibits a weakened basal texture and thus excellent mechanical properties.